2011
DOI: 10.2337/dc11-0294
|View full text |Cite
|
Sign up to set email alerts
|

High Plasma Level of Fibroblast Growth Factor 21 Is an Independent Predictor of Type 2 Diabetes

Abstract: OBJECTIVETo investigate whether circulating levels of fibroblast growth factor 21 (FGF21), which previously has been shown to be elevated in obesity, could predict the development of type 2 diabetes in a 5.4-year, population-based, prospective study.RESEARCH DESIGN AND METHODSBaseline plasma FGF21 levels were measured using an enzyme-linked immunosorbent assay in 1,900 subjects from the Hong Kong Cardiovascular Risk Factor Prevalence Study (CRISPS). The prospective association of FGF21 with diabetes developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
146
4
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(165 citation statements)
references
References 15 publications
12
146
4
3
Order By: Relevance
“…In the present study, baseline plasma samples were available for FGF21 measurement from 9697 (99.0%) out of 9795 patients from the FIELD study. FGF21 levels were measured using enzyme-linked immunosorbent assay kits (Antibody and Immunoassay Services, University of Hong Kong, Hong Kong) as described previously [7,12,17]. Briefly, a 60 μl plasma sample was diluted 1:1 (vol.:vol.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, baseline plasma samples were available for FGF21 measurement from 9697 (99.0%) out of 9795 patients from the FIELD study. FGF21 levels were measured using enzyme-linked immunosorbent assay kits (Antibody and Immunoassay Services, University of Hong Kong, Hong Kong) as described previously [7,12,17]. Briefly, a 60 μl plasma sample was diluted 1:1 (vol.:vol.)…”
Section: Methodsmentioning
confidence: 99%
“…FGF21 regulates peroxisome proliferator-activated receptor-γ (PPAR-γ ) and the glucose-l ow ering acti vi ty of thiazolidinediones [3,4]. Despite these beneficial effects of FGF21 in glucose metabolism in animal studies, circulating FGF21 levels are often elevated in obesity, dyslipidaemia, insulin resistance, type 2 diabetes and coronary artery disease [2,[5][6][7]. The elevation in FGF21 levels may be a compensatory response to underlying metabolic stress or may be due to impaired FGF21 signalling leading to FGF21 resistance [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, raised FGF21 levels have been found in various cardiometabolic conditions in clinical studies, suggesting a reactive change to FGF21 resistance or the underlying metabolic disturbances 1. In population studies, we and others had previously shown that high circulating FGF21 levels predicted the development of type 2 diabetes mellitus (T2DM) and were associated with carotid atherosclerosis independent of established cardiovascular risk factors 5, 6, 7, 8, 9. Among subjects with T2DM, recently, we also demonstrated that serum FGF21 levels predicted nephropathy progression, in terms of decline in estimated glomerular filtration rate (eGFR), even in the stage of normoalbuminuria and relatively preserved renal function, highlighting its potential use as an early biomarker for diabetic kidney disease, a devastating diabetic complication 10…”
Section: Introductionmentioning
confidence: 99%
“…5-HT2C receptordeficient mice fed a high-fat diet rapidly develop obesity, insulin resistance, and type 2 diabetes [23]. 5-HT2C receptors expressed by POMC neurons are physiologically relevant regulators of insulin sensitivity and glucose homeostasis in the liver [24].…”
Section: Discussionmentioning
confidence: 99%